2009
DOI: 10.1039/b912324e
|View full text |Cite
|
Sign up to set email alerts
|

The role of water in the synthesis and performance of vapour phase polymerised PEDOT electrochromic devices

Abstract: Parameters affecting the quality of vapour phase polymerised (VPP) PEDOT and their influence on electrochromic device performance were investigated. Specifically, the role of water during synthesis was examined and a polymerisation mechanism proposed. Paradoxically, water vapour is essential for PEDOT polymerisation, however, too high a loading leads to crystallite formation in the oxidant layer, rendering the oxidant inactive. Changes in water vapour affect the doping level of the polymer, presumably due to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
79
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(82 citation statements)
references
References 43 publications
(58 reference statements)
2
79
0
1
Order By: Relevance
“…[29,30] Mobility of the oxidant is important to the VPP process, given the requirement for transport of these ions to the liquid-vapor interface to facilitate further polymerization to occur. [31,32] Changes in the coordination between iron, tosylate and water have been shown to have large effects on the polymerization kinetics.…”
Section: The Effect Of Uv Light On the Oxidantmentioning
confidence: 99%
“…[29,30] Mobility of the oxidant is important to the VPP process, given the requirement for transport of these ions to the liquid-vapor interface to facilitate further polymerization to occur. [31,32] Changes in the coordination between iron, tosylate and water have been shown to have large effects on the polymerization kinetics.…”
Section: The Effect Of Uv Light On the Oxidantmentioning
confidence: 99%
“…[25][26][27][28][29][30][31][32][33] These oxidants are also easily crystallized during the reaction due to their low solubility, and the crystallized oxidants cause the formation of pin-hole defects in the film. 34 The loading of PEPG further reduces the film thickness due to a severe concentrating effect. A low thickness results in both a high internal resistance that limits the power output as a TE device 36 and a high square resistance that is not viable for electrode materials.…”
Section: Introductionmentioning
confidence: 99%
“…A low thickness results in both a high internal resistance that limits the power output as a TE device 36 and a high square resistance that is not viable for electrode materials. Although multiple fabrications could be used to obtain thicker films, that process may not only generate layer-layer interfaces due to the disconnected polymer chains and nonuniformity along the layer growth direction 31,33,34 but also cause the decomposition of the formerstep-deposited layers by re-heating.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fabretto et al have reported on the role of water during PEDOT polymerization via VPP. 40 Water was introduced into the polymerization chamber to vary relative humidity from 10 to 70% and films were compared according to conductivity. Substrates pretreated with Fe(III) tosylate as an oxidizing agent were unable to grow polymer films without the presence of any water vapor.…”
Section: Reviewmentioning
confidence: 99%